In Vitro Antioxidant Evaluation of Extracts of Three Wild Malaysian Plants - Muhammad, Khan; Norasyidah, Harun; Azhari, H. Nour; Elhussein, Salah A. A. (Elsevier Ltd, 2013)
The aim of this study is to evaluate the antioxidant activity of three species commonly available in Malaysia. Mimosa pudica and Crotalaria pumila belongs to family Febaceae while Lantana camara, belongs to Verbenaceae. The extracts were prepared by Soxhlet extraction method using ethanol as a solvent. The -carotene bleaching assay and 1,1-Diphenylpicrylhydrazyl (DPPH) radical scavenging method were used to determine antioxidant properties of plants by measuring decrease in absorbance at 470 nm and 517 nm to calculate percent inhibition of each specie. The antioxidant activity was then compared with standard Butylated hydroxyanisole (BHA). Among three samples M. Pudica showed the highest total antioxidant activity 58% compared with other samples. Crotalaria exhibited good antioxidant activity and free radical scavenging activities 54% while lantana showed the weaker antioxidant activity 19%.